2020
DOI: 10.1016/j.sjbs.2020.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced modulation of gut microbial dynamics affecting body weight in birds triggered by natural growth promoters administered in conventional feed

Abstract: This study explored the effects of natural growth promoters (phytogenic feed additives and organic acids) on animal performance, carcass characteristics, blood parameters, gut microflora composition, and microbe–host interactions in broiler chickens over a 42-day feeding period. Two-hundred-fifty-day-old chicks were randomly assigned to one of five treatments: (i) control diets (CON); (ii) control diets + 40 g/tons antibiotic growth promoter (AB); (iii) control diets + 3 kg/tons organic acids (ORG); (iv) contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…Many studies have been conducted to illustrate the effect of cinnamon on blood biochemical profile, including antioxidant activity, lipid profile and immunity. The cinnamon-based PFAs group exhibited significant differences in albumin/globulin (A/G) ratio and cholesterol concentrations as compared to control treatments [1]. Additionally, non-significant interactions were found for total protein, globulin levels and serum albumin among treatments.…”
Section: Cinnamon and Blood Biochemical Profilementioning
confidence: 96%
See 2 more Smart Citations
“…Many studies have been conducted to illustrate the effect of cinnamon on blood biochemical profile, including antioxidant activity, lipid profile and immunity. The cinnamon-based PFAs group exhibited significant differences in albumin/globulin (A/G) ratio and cholesterol concentrations as compared to control treatments [1]. Additionally, non-significant interactions were found for total protein, globulin levels and serum albumin among treatments.…”
Section: Cinnamon and Blood Biochemical Profilementioning
confidence: 96%
“…The global production of chicken meat reached about 137 million tons in 2020, making poultry the most consumed meat in the world. Therefore, the poultry industry contributes significantly to animal protein consumption and to human nutrition and global food security [1]. In recent years, significant improvements have been made to improve poultry health and performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, it is essential to find viable and potential alternatives for sustainable poultry production. Thus, extensive research is now focused on searching the alternative to AGPs with similar antimicrobial and growth-enhancing potential in broiler chickens [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This ability to improve growth may be attributed to the presence of phytochemicals such as flavonoids, phenols, saponins and alkaloids that are known to perform multiple biological functions including favoring growth of beneficial bacteria (Enterococcus spp, Lactobacillus spp.) that are positively correlated with weight gain (Oluwafemi et al, 2020;Rashid et al, 2020). Moreover, the ability of C. frutescens powder to improve growth at 2.2% inclusion level makes it comparable to other phytogenic feed additives that have achieved similar effects such as tannins from Quebracho (Marzoni et al, 2020) and coriander (Abou-Elkhair et al, 2014), Further, positive effects on growth have also been reported for several phytogenic feed additives when included at lower levels such as 0.2, 0.25, 0.5, 0.75%, for chicory, Myristica fragrans, turmeric and red pepper extract respectively (Khoobani et al, 2020;Adu et al, 2020;Abou-Elkhair et al, 2014;Islam et al, 2018).…”
Section: Body Weightmentioning
confidence: 99%